PCR Ribotyping for Determining the Diversity of Some Clinical Pseudomonas Aeruginosa Isolates - Hassan, Khulod Ibraheem; Abdullah, Saman Rafeeq; Hawrami, Khidir (Al-Nahrain Journal of Science, 2018)
To study the genetic diversity between deferent strains of P. aeruginosa, this study was carried out between August and December 2010 by collecting 165 clinical samples from wounds, burn, ear and urinary tract infection taken from general hospitals of Sulaimani, Erbil and Koya governorates. After identifying P. aeruginos based upon culture methods using the selective media (cetrimide agar) coupled with biochemical tests, Polymerase chain reaction (PCR) method were used for identifying P. aeruginosa using primers targeting 16S rRNA. PCR analysis of 16S-23S internal transcribed spacer primer targeting the interspaced regions between the 16 and 23S rRNA genes (PCR ribotyping) was evaluated for it s effectiveness to differentiate between the isolates, the results show that the clinical isolates of P. aeruginosa belongs to three ribotypes, which were showed in one to three bands in each isolate of P. aeruginosa.